The Functions and Mechanisms of Basic Fibroblast Growth Factor in Tendon Repair - Lu, Jingwei; Jiang, Li; Chen, Yixuan; Lyu, Kexin; Zhu, Bin; Li, Yujie; Liu, Xueli; Liu, Xinyue; Long, Longhai; Wang, Xiaoqiang; Xu, Houping; Wang, Dingxuan; et al. (Frontiers in Physiology, 2022)
Tendon injury is a disorder of the musculoskeletal system caused by overuse or trauma, which is characterized by pain and limitations in joint function. Since tendon healing is slowly and various treatments are generally ineffective, it remains a clinically challenging problem. Recent evidences suggest that basic fibroblast growth factor (bFGF) not only plays an important role in tendon healing, but also shows a positive effect in clinical practice. The purpose of this review is to summarize the effects of bFGF in the tendon healing. Firstly, during the inflammatory phase, bFGF stimulates the proliferation and differentiation of vascular endothelial cells to foster neovascularization. Furthermore, bFGF enhances the production of pro-inflammatory factors and thus accelerates tendon repair. Secondly, the cell proliferation phase is accompanied by the synthesis of a large number of extracellular matrix components. bFGF speeds up tendon healing by stimulating fibroblasts to secrete type III collagen. Lastly, the remodeling phase is characterized by the transition from type III collagen to type I collagen, which can be promoted by bFGF. However, excessive injection of bFGF can cause tendon adhesions as well as scar tissue formation. In future studies, we need to explore further applications of bFGF in the tendon healing process.